Przeciwko autorytetowi tekstu II: „Anatomia Tytusa" Heinera Mullera i performatywny wymiar tekstu dla teatru - Borowski, Mateusz (Przestrzenie Teorii, 2008)
Muller's manifold critical relationship with the tradition of playwriting allows seeing his Anatomy Titus Fall of Rome as a borderline case between the canonical form of drama and the text understood as the raw material for the stage. The complex structure of Muller's text may serve as a good material for demonstrating that the structure of the text for the stage is always conditioned on the one hand by the dominant theatre conventions and on the other hand by the receptive habits of the audience. The main objective of the present essay is to demonstrate that the theatrical character of a text is not an immanent feature of its form, but rather it is a manner of reading this text in a specific historical and theatrical context, with a specific purpose in view.